Islam as Unifier and Divider in Politics and Nation-Building in Modern Sudan - Nabilul Maram, Ahmad; Hotimah, Husnul; Aulia Bagas Satriya (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2025)
This article analyzes the dual role of Islam in Sudan’s modern history, emphasizing its capacity to unify communities while simultaneously deepening political and social fragmentation. Covering the period from independence in 1956 to the present conflict, it traces how Islamic references shaped legitimacy, governance, and violence. The study employs a qualitative and historical-critical method, drawing on constitutions, Sharia statutes, scholarly works, international reports, and archival news, with triangulation and process tracing ensuring reliability and contextual depth. The findings demonstrate that Islam has repeatedly been instrumentalized to consolidate political power. Early on, Sufi networks such as the Ansar and Khatmiyya promoted cohesion but also entrenched rivalries that destabilized politics. Under Jaafar Nimeiri and the National Islamic Front, state-led Islamization, epitomized by the September Laws, institutionalized exclusivity and marginalized both non-Muslims and dissenting Muslims. This framework intensified conflicts in Darfur and South Sudan, linking Islamization to displacement, atrocities, and gender-based violence. By contrast, inclusive Islamic discourses stressing justice and Maqasid al-Shariah fostered civic trust and opened pathways for negotiation, as reflected in the Juba Peace Agreement. After the 2019 revolution, reforms aimed at separating religion from the state suggested a shift toward inclusivity. Yet renewed war reopened avenues for political instrumentalization: the Sudanese Armed Forces drew on Islamist currents to revive jihadist rhetoric, while the Rapid Support Forces positioned themselves as anti-Islamist actors mixing religious symbolism with secular claims. These dynamics reveal the enduring malleability of Islam in Sudanese politics. The study concludes that inclusive framings encourage unity, while monopolization entrenches division, situating Sudan’s experience within broader debates on religion, authoritarianism, and nation-building in divided societies.